Sentencing ‘Anonymous’: exacerbating the civil divide between online citizens and government. - Tomblin, Jordon; Jenion, Greg (Police Practice & Research, 2016)
The rise of the hacktivist collective Anonymous and its activities have led to a number of international high profile arrests and criminal sentences. In Canada, birth cohort studies and the established age–crime curve consistently show that even in the absence of intervention the majority of offenders desist in offending as they age. We argue that criminal justice responses need to be restrained and policy makers need to consider the measureable harm of virtual protests. We anticipate that failure to do so will result in produced criminalization effects that are more reflective of a societal overreaction on the part of authorities. In conclusion, we reflect on the responses to activity akin to civil protest carried out in defense of liberty and argue contemporary trajectories will only exacerbate a civil divide between those who believe a system is corrupt and failing and those whose job it is to maintain law and order.